Analysis of the effectiveness of the portal integrating various tender platforms - Jedynak, Adrian Krzysztof; Miłosz, Marek (Journal of Computer Sciences Institute, 2025)
The article presents an analysis of the efficiency of a portal integrating various tender platforms. The study identifies key factors affecting the effectiveness and functionality of such platforms, including search speed, integration with external databases, and user settings customization. Three popular portals were evaluated in terms of usability, information accessibility, reliability, and technical support. The results highlight the strengths and weaknesses of each platform, indicating areas for improvement to enhance efficiency and user satisfaction.